Accessing Aryldifluoromethyl Derivatives through Alkene Insertion into Benzylic C–F Bonds - You, Mengwei; Bian, Tiancen; Zhou, Liejin; Zhang, Zuxiao (Synlett, 2023)
We report our formal insertion of alkenes into benzylic C–F bonds of electron-deficient perfluoroalkylarenes under organophotocatalytic conditions with Et3N·3HF as an external fluoride source. The absence of a fluoride scavenger or other external reductant permits the formation of a carbocation and its trapping by other nucleophiles. This three-component reaction represents one of the most efficient methods for preparing a variety of complex partially fluorinated organic molecules. This redox-neutral transformation features mild conditions, a broad substrate scope, and extraordinary functional-group tolerance. Moreover, several examples of modifications of complex drug molecules further demonstrated its utility.
Keywords: photocatalysis; organocatalysis; aryldifluoromethyl compounds; late-stage functionalization; C–F bond cleavage; radical–polar crossover reaction